2
$\begingroup$

Solve the following system of equations for $x,y,z$ as $a,b,c\in\Bbb{R}$

\begin{align*}xy+yz&=a^2\tag{1}\\xz+xy&=b^2\tag{2}\\yz+zx&=c^2\tag{3}\end{align*}

My try: Assume that $x,y,z\ne 0$ (it is easy to check the case where some are zero).

Subtract first equation from second equation we will get the system \begin{align*}xz-yz&=b^2-a^2\\xz+yz&=c^2\end{align*} Adding and subtract both equations we get $$x=\frac{b^2+c^2-a^2}{2z},y=\frac{a^2+c^2-b^2}{2z}$$I tried to set the expressions into one of the equations and get value of $z$, but it got quiet messy.

Is there any easier way of solving the system?

Any help will be appreciated, thanks!

$\endgroup$
5
$\begingroup$

Adding we get $$2(xy+yz+zx)=a^2+b^2+c^2$$

$$2xy=a^2+b^2+c^2-2c^2=a^2+b^2-c^2$$ etc.

Muliplying we get $$8x^2y^2z^2=\prod_{\text{cyc}}(a^2+b^2-c^2)$$

$$xyz=\pm\sqrt{\dfrac{\prod_{\text{cyc}}(a^2+b^2-c^2)}8}$$

and $xy=\dfrac{a^2+b^2-c^2}2$

$$z=\dfrac{xyz}{xy}=?$$

$\endgroup$
  • $\begingroup$ I don't understand the notation $\displaystyle\prod_{\text{cyc}}$. $\endgroup$ – Galc127 Jul 13 '16 at 8:07
  • 1
    $\begingroup$ @Galc127, $$\prod_{\text{cyc}}(a^2+b^2-c^2)$$ $$=(a^2+b^2-c^2)(b^2+c^2-a^2)(c^2+a^2-b^2)$$ $\endgroup$ – lab bhattacharjee Jul 13 '16 at 8:08
0
$\begingroup$

In M2

S=QQ[a,b,c]
FS=frac S
R=FS[x,y,z]
I=ideal(x*y+y*z-a^2,x*z+x*y-b^2,y*z+z*x-c^2)
gens gb I -- | y+(a2+b2-c2)/(a2-b2-c2)z x+(-a2-b2+c2)/(a2-b2+c2)z z2+(a4-2a2b2+b4-c4)/(2a2+2b2-2c2) |
$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.